Pengembangan Electronic Government Si Cakman dalam Mewujudkan Kepastian Layanan di Lembaga Pemasyarakatan Kelas IIA Sidoarjo - Herfizal, Lorita Nafizatus; Kriswibowo, Arimurti (Journal of Education on Social Science (JESS), 2024)
In line with the growing demands for excellent public service delivery, Class IIA Correctional Institution Sidoarjo as one of the Correctional Technical Implementation Units in East Java participated in trying to improve service quality through the idea of digital bureaucracy by implementing the concept of e-government and creating an online-based public service product, namely Si Cakman or Innovation Track Delivery. However, in implementing Si Cakman, Class IIA Correctional Institution Sidoarjo still faces various challenges and obstacles. The research aims to find out, analyze and describe the successful elements of Si Cakman e-government development in realizing service certainty at Class IIA Correctional Institution Sidoarjo using the theory of successful elements of e-government development based on the results of studies and research from the Harvard JFK School of Government. This research uses descriptive qualitative research with a case study approach. Data collection techniques through interviews, observation and documentation. The results showed that the development of Si Cakman e-government at Class IIA Correctional Institution Sidoarjo can be said to be quite successful, this can be seen from the support of the vision and mission and socialization, the availability of technological infrastructure, and the benefits felt by all related parties. However, in its application there are shortcomings in terms of policy, availability of financial resources and human resources, improvements are needed so that the implementation of e-government Si Cakman can run optimally.